Reception of the Internal Law of Religious Associations in the Provisions of Polish Law Concerning Marriage and Respect for the Principle of Autonomy and Mutual Independence of the State and the Church - Tunia, Anna (Prawo Kanoniczne, 2025)
The subject of this article is the problem of reception of the norms of the law of religious associations into Polish law, which is considered in the context of respect for the principle of autonomy and mutual independence of the state and the church, guaranteed in the Constitution of the Republic of Poland (Article 25, paragraph 3). The author indicates in it that in a democratic state of law, guaranteeing autonomy and mutual independence of state and church structures, the phenomenon of reception of the internal law of religious associations in state law may occur. The method of conducting this reception and its scope are problematic. The analyses presented in the article concern cases of reception in the area of matters concerning the conclusion of civil marriages in a religious form. Reception is examined in the scope of the official entity of the conclusion of marriage, declarations of will on obtaining civil effects of canonical marriage and the form of conclusion of this marriage. The author indicates whether and what type of reception takes place in individual cases and assesses whether this reception is justified and whether its application in a given case does not threaten the security of legal transactions.